Public Opinion on the Pring Sewu Cultural Market in Binangun Hamlet - Nurrafi, Deajeng; Rochmaniah, Ainur (Procedia of Social Sciences and Humanities, 2024)
Communication is a basic human activity, by communicating humans can relate to each other in everyday life wherever humans are. Intrapersonal communication is a communication process that occurs within a person. This communication involves an individual's thoughts, feelings and perceptions of something. The Pring Sewu Cultural Market exists as an effort to preserve local cultural values. This research aims to understand how society responds to unique market innovations, such as the use of bamboo coins as a transaction tool. This cultural market is a local initiative that aims to preserve and promote cultural heritage and support the local economy. This research uses qualitative methods. Data was collected through interviews, observation and documentation. In this research, the majority of public opinion agrees with the existence of a cultural market. Some people appreciate cultural activities as a way of preserving local traditions, while others criticize them because they are deemed not in accordance with the community's social values. The results of this research provide a positive response to the existence of the Pring Sewu Cultural Market, the majority of people are of the opinion that they provide many ideas or input for the Pring Sewu market, such as making trash cans from bamboo, adding traditional food menus and collaborating with local residents to create art performances.